2008
DOI: 10.1164/rccm.200801-136oc
|View full text |Cite
|
Sign up to set email alerts
|

Rhinovirus Disrupts the Barrier Function of Polarized Airway Epithelial Cells

Abstract: Rationale : Secondary bacterial infection following rhinovirus (RV) infection has been recognized in chronic obstructive pulmonary disease. Objectives: We sought to understand mechanisms by which RV infection facilitates secondary bacterial infection. Methods : Primary human airway epithelial cells grown at air-liquid interface and human bronchial epithelial (16HBE14o-) cells grown as polarized monolayers were infected apically with RV. Transmigration of bacteria (nontypeable Haemophilus influenzae and others)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
312
5
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(339 citation statements)
references
References 43 publications
11
312
5
3
Order By: Relevance
“…23 In the human nasal mucosa, the virus infection causes the loss of ZO-1 from tight junction complexes, and the loss leads to intranasal bacterial inoculation in mice. 24 In our study, the mRNA and protein expression levels of ZO-1 and E-cadherin were decreased in hypoxia-stimulated NHNE cells. This is the first study to reveal a relationship between hypoxia and barrier dysfunction in upper airway epithelial cells by analyzing the expressions of ZO-1 and E-cadherin in the normal and hypoxic human nasal mucosa.…”
Section: Discussionsupporting
confidence: 50%
“…23 In the human nasal mucosa, the virus infection causes the loss of ZO-1 from tight junction complexes, and the loss leads to intranasal bacterial inoculation in mice. 24 In our study, the mRNA and protein expression levels of ZO-1 and E-cadherin were decreased in hypoxia-stimulated NHNE cells. This is the first study to reveal a relationship between hypoxia and barrier dysfunction in upper airway epithelial cells by analyzing the expressions of ZO-1 and E-cadherin in the normal and hypoxic human nasal mucosa.…”
Section: Discussionsupporting
confidence: 50%
“…tract, but once colonization is established, NTHi can become pathogenic itself, or contribute to the pathology of other bacteria (10) or of viral infections that lead to increased bacterial biomass (54). It can also disrupt epithelial tight junctions, which allows bacterial invasion (55). It is possible that steroid-suppression of MAIT cells could also contribute to this initial colonization step in COPD and other airway diseases.…”
Section: Cd161mentioning
confidence: 99%
“…Sajjan et al (2008) showed that infection of polarized airway epithelial cells with HRV can lead to redistribution of the tight junction protein zona occludens 1 (ZO-1) from the membrane to the cytoplasm. Furthermore, HRV was shown to impair the repolarization of airway epithelium regenerating after injury (Faris et al, 2016).…”
Section: Compromising the Epithelial Barrier Functionmentioning
confidence: 99%